Upgrading the ICT Regulatory Framework: Toward Accelerated and Inclusive Digital Connectivity - Ramonette B. Serafica; Queen Cel A. Oren (Philippine Institute for Development Studies (PIDS), 2022)
Across different metrics, the ICT performance of the Philippines remains subpar compared to ASEAN members and other countries at the same level of development. The quality of the country's ICT regulatory environment, composed of regulatory authority, regulatory mandate, regulatory regime, and competition model, is significantly below what is considered international best practice, consequently impeding the use of various technological solutions available to bridge the gap in digital inequality. Although significant policy changes have recently been introduced, more reforms are needed to achieve inclusive and accelerated digital connectivity. Priorities include reforming the licensing regime, formulating a spectrum policy and plan, and reinventing the NTC to ensure regulatory independence.
Keywords: 330; ICT; telecommunications; digital; regulation; broadband